A Narrative Approach to Discerning Some Key Issues for Catholic Education in a More Synodal Church - Richard Rymarz (Religions, 2023)
Synodality is described as a mentality that esteems three actions: encountering, listening. and discerning. This mentality is applied to a discourse on Catholic education premised on three illustrative narratives. Narratives are used as a suitable instrument to gain deep insights into the lived experience of teachers working in Catholic schools. Several concurrent themes are identified as emerging issues for a more synodal church. These include challenges in providing enough teachers to animate the religious identity of schools. This is linked to profound changes in patterns of religious affiliation that have been evident for several decades. Considering this, acknowledgement needs to be made that the lived experience of teachers entering Catholic education today is distinctive and different from previous generations. In light of this, a number of points of discernment are made. These include the need for ongoing, nuanced teacher recruitment and formation, as well as a reconceptualization of religious education (RE) to take into account changing cultural dynamics and providing more practical support for teachers, especially RE teachers.